Optimization of Image Quality Parameters of Cranium Examination to Prevent Radiograph Repetition - Nisa, Chairun; Yudha, Sagita; Hanifah, Wahdini; Nansih, Livia Ade; Ibrahim, Ohana Yanisa (Oshada, 2026)
Cranium radiography technique is a technique of depicting the cranium using X-rays to obtain radiographs to help establish a diagnosis. In cranium examination, high sharpness and detail are required so that the information obtained on the radiograph is clearly visible. On the other hand, exposure factors, namely tube voltage, tube current, time, and the Focus Film Distance (FFD) factor as well as the width of the radiation field are very important so that the desired object is visualized correctly and well and to avoid repeat radiographs. The purpose of this study is to find a reference for optimizing the mAs exposure factor in Cranium Examination.to prevent repeat radiographs.This research method is quantitative experiment. The research sample in the form of a cranium phantom was exposed three times with variations of mAs 16, 20, and 25 at a constant voltage of 60 kV to obtain optimal image results. Based on histogram analysis, mAs 16 produces a more even distribution of intensity values ​​and more optimal contrast compared to mAs 20 and 25. Therefore, mAs 16 is the most efficient variation for AP projection cranium examination because it is able to produce good diagnostic image quality with a low radiation dose.